Computational Thinking Evaluation Tool Development for Early Childhood Software Education - Lee, Kyunghee; Cho, Jungwon (Society of Visual Informatics, 2021)
The early childhood software education is being actively conducted, but research on evaluation of computational thinking is in its infancy. The purpose of early childhood software education is to cultivate the computational thinking through activities centered on solving problems in everyday life. Evaluation in software education is very important in that it not only measures computational thinking simply but also improves computational thinking through evaluation. As such, guidelines for evaluating computational thinking that can be used in early childhood software education are needed, but they are very lacking. Therefore, in this study, the researcher developed an evaluation tool that can meet the ultimate purpose of software education, cultivating computational thinking. The developed evaluation tools are a software education effectiveness test tool and a computational thinking test tool. They were developed to the level of development and interaction of the early childhood. The developed evaluation tool has been validated by software experts, early childhood education experts, and early childhood teachers. As a result of the second step validity verification, all content validity was confirmed. Through this, it was confirmed that the evaluation tool developed in this study can be used as a tool for evaluating computational thinking. This study provides implications for evaluation of computational thinking for early childhood software education. In addition, it is meaningful that it has been suggested to be effectively used for proper evaluation in early childhood software education.